Making a Database Product Self-Sustain: The Experience of TEXINCON - Shah, P.C.; Sitwala, K.C. (DESIDOC Journal of Library & Information Technology, 2002)
TEXINCON is a bibliographic database, containing self explanatory summaries of articles, developments, books, standards, etc in the field of textile and allied subjects, being produced by Ahmedabad textile industry's research association. The contents, management, publicity, marketing and sales efforts being done for TEXINCON have been covered in this article. http://dx.doi.org/10.14429/dbit.17.4.3226